2019
DOI: 10.1177/0391398819837546
|View full text |Cite
|
Sign up to set email alerts
|

Additional hemoperfusion is associated with improved overall survival and self-reported sleep disturbance in patients on hemodialysis

Abstract: Introduction: Patients with maintenance hemodialysis have experienced long-standing sleep disturbance. In this study, we attempted to explore whether long-term hemoperfusion could improve sleep and increase the overall survival in hemodialysis patients. Methods: A total of 158 patients, who underwent routine hemodialysis, were assessed in this study. These patients were computer-matched into two groups, with one group including 80 patients with absolute hemodialysis and the other consisting of 78 cases with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The reduction in urea and creatinine concentration was found, and the hematological indices did not change after each dialysis session (Table 2). Some previous studies showed that long-term combination of hemodialysis and HP effectively improved uremia complicated with bone and mineral disorders [31] and also improved sleep and increased the overall survival [32]. The results of our study once again confirmed that the combination of HD and HP reduced the manifestations related to calcium, phosphates, and PTH metabolic disorders and especially reduce the death rate due to cardiovascular events.…”
Section: Discussionsupporting
confidence: 85%
“…The reduction in urea and creatinine concentration was found, and the hematological indices did not change after each dialysis session (Table 2). Some previous studies showed that long-term combination of hemodialysis and HP effectively improved uremia complicated with bone and mineral disorders [31] and also improved sleep and increased the overall survival [32]. The results of our study once again confirmed that the combination of HD and HP reduced the manifestations related to calcium, phosphates, and PTH metabolic disorders and especially reduce the death rate due to cardiovascular events.…”
Section: Discussionsupporting
confidence: 85%
“…Besides meeting the primary outcome, patients in the combined hemodialysis and hemoperfusion group demonstrated better amelioration of pruritus and better sleep quality. Additionally, biochemical parameters such as calcium and phosphorus showed improvement [59]. The study findings are reassuring and provide a means of symptom control for those who dislike taking medications or are concerned about polypharmacy.…”
Section: Altering Membrane Fluxmentioning
confidence: 51%
“…In the countries that use low-flux HD as the basic HD regimen for HD patients, HD + HP would still have important benefits by improving various laboratory and clinical outcomes when compared with low-flux HD. [25][26][27][28][29][30] In the communities that utilize HDF as the main HD treatment, HD + HP with conventional prescription of low BFR during the first 2 h of the procedure might not yield significantly additional advantages to the patients when compared with HDF.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30] Although there was an earlier suggestion that HD + HP might be more effective than HDF in removing uremic toxins, 25 there have no studies directly comparing between HD + HP and real high-volume postdilution olHDF. [25][26][27][28][29][30] On the contrary, indirectly comparative data showed that HD + HP might yield inferior uremic toxin-removing efficacy to high-volume postdilution ol-HDF. [25][26][27] In the present study, we examined whether an integration of HP into the HD + SHF circuit (HD + SHF + HP) could provide better removal of various uremic toxins than high-volume postdilution ol-HDF using high-flux dialyzer.…”
Section: Introductionmentioning
confidence: 99%